Adherence to Symptom-Based Care Guidelines for Down Syndrome. (February 2017) - Santoro, Stephanie L.; Yin, Han; Hopkin, Robert J.
To assess adherence to symptom-based studies recommended in the health supervision guidelines for Down syndrome from the American Academy of Pediatrics (AAP), 24 pediatric care sites participated in retrospective chart review. Symptom-based screening and 4 associated recommendations, including cervical spine radiograph, video swallow study, celiac study with tissue transglutaminase and sleep study were analyzed by reviewing well-child visit notes of 264 children with Down syndrome. Given trends toward symptom-based screens, Pearson's chi-square test and Fisher's exact test were used to determine the association between symptom presence and receiving corresponding symptom-based screens. Adherence rates were widely variable ranging from 0% to 79% completion. Symptom-based studies were performed in 22% to 36% of patients. Symptom screens were documented positive in many patients, but the presence of symptoms did not correlate with completion of symptom-based screens. Symptom-based screening is low; associated studies were performed in patients without documented symptoms contrary to AAP recommendation.